Means to achieve social interaction in green open space in Baghdad, Iraq - Salih, Sarah Abdulkareem (Zes Rokman Resources, 2017)
Since the war of 2003 and Baghdad suffers in different levels political, administrative, economic ethnic, sectarian, etc. That led to the loss of lives, social capital, increased crisis aggravation between different ethnic, and destruction a lot of open space and recreational places in Baghdad nowadays. Therefore this paper addresses the issue of lack of social interaction among Baghdad residents as a result of lack in open spaces and recreational activities. Thus the main objective of the paper is to determine the means to enhance sound social interaction for community of Baghdad in green open spaces through identifying criteria and factors of open spaces in general to support social interaction and community. This paper employs qualitative content analysis method which mainly focused on collecting summarizing and analyzing various documentation such as (writing journals, articles, researches, books, Web sites, manifestos, transcripts and figures) from more than 30 source, regarding the importance of public open spaces for the community. Content analysis of the paper is the fundament for a qualitative oriented procedure of text interpretation used to summarize and analyze the information gathered. Results of this study confirms that sound social interaction in general requires an appropriate physical space (could be green open space) which includes such criteria: design, activities, elements, access and linkage, safety and security, administration and maintenance, and users' characteristics, also previous studies in this area emphasize that the responsible authorities need to make redouble efforts in order to address the issue of existing parks in Baghdad nowadays.